Exploring the Well-being of First-Year Guidance and Counseling Students in Educational Settings - Awalya Siska Pratiwi; Ella Faridati Zen; Syaza Naijah Binti RahimSyazanajihah (Universitas Pendidikan Ganesha, 2025)
Student well-being is a crucial factor influencing academic engagement, psychological adjustment, and overall success in higher education, particularly during the first year of study when students face significant academic and social transitions. First-year students often experience challenges such as adapting to new learning environments, managing academic demands, and building social connections, which can affect their psychological well-being. This study aims to analyze and explore the level of well-being among first-year students in the Guidance and Counseling program. Using a survey design, the research involved 188 active first-year students selected from five student cohorts. Data were collected through an online questionnaire consisting of 18 items measured on a 4-point Likert scale, and analyzed descriptively. The results indicate that 77% of students fall within the moderate category of well-being, 20% in the high category, and 3% in the low category. Conceptually, these findings suggest that the majority of students maintain an adequate level of psychological well-being, yet there remains a considerable proportion requiring targeted support. The study concludes that enhancing responsive self-development programs is essential to strengthen the psychological well-being of first-year students during their academic transition.